Associations of maternal periconceptional alcohol consumption with offspring prehypertension/hypertension at age 6 years: the Growing Up in Singapore Towards healthy Outcomes prospective mother-offspring cohort study. Issue 6 (June 2022) - Sadananthan, Suresh Anand; Michael, Navin; Tint, Mya Thway; Thirumurugan, Kashthuri; Yuan, Wen Lun; Ong, Yi Ying; Law, Evelyn; Choo, Jonathan; Ling, Lieng Hsi; Shek, Lynette; Fabian, Yap; Tan, Kok Hian; et al.
Abstract : Objective: To evaluate the relationship of the levels of maternal alcohol consumption during the 1 year before pregnancy recognition with childhood cardiorenal, metabolic, and neurocognitive health. Methods: In 1106 women and their children from the Growing Up in Singapore Towards healthy Outcomes mother-offspring cohort, quantity of maternal alcohol consumption in the 12 months prior to pregnancy recognition was categorized as high (≥75 th percentile: 1.9 g/day), low (<1.9 g/day), and none, and frequency of alcohol consumption was categorized as high (≥2–3 times/week), low (<2–3 times/week), and none. Offspring MRI-based abdominal fat depot, kidney, and brain volumes, blood pressure, metabolic syndrome score, and cognitive intelligence scores were assessed. Child prehypertension/hypertension at age 6 years was defined using a simplified pediatric threshold of 110/70 mmHg. Results: The average maternal alcohol consumption in the year prior to pregnancy recognition was 2.5 g/day, which is lower than the daily maximal limit of one standard drink (10 g) recommended for women by Singapore's Ministry of Health. After adjusting for participant characteristics, alcohol consumption at least 1.9 g/day was associated with over two-fold higher risk (risk ratio = 2.18, P  = 0.013) of child prehypertension and 15% greater kidney growth between early infancy and age 6 years ( P  = 0.040) compared with abstinence. Alcohol consumption was not associated with metabolic and neurocognitive health at age 6–7 years. The associations with high frequency of alcohol consumption were concordant with those obtained for quantity of alcohol consumption. Conclusion: Maternal self-reported alcohol consumption at least 1.9 g/day prior to pregnancy recognition was associated with increased risk of child prehypertension and rapid kidney growth. Our findings highlight the potential detrimental effects of low periconceptional alcohol consumption, below national guidelines on offspring cardiorenal health.